Un wiki sémantique pour l’édition scientifique d’une correspondance du xixe siècle - Bertrand Duménieu; Danièle Poublan; Jean-Damien Généro; Francine Filoche; Patricia Bleton (Humanités Numériques)
The lettresfamiliales.ehess.fr website is a semantic wiki presenting an updated and augmented version of the corpus of letters written by the Mertzdorff-Duméril-Froissart family. This family includes scientists from the National Museum of Natural History in Paris, textile manufacturers and high rank civil and military officials whose social ascension took place between the end of the 18th century and the beginning of the 20th century. Their correspondence is a powerful tool of sociability, a means to increase their social status and, for us, a way to keep track of their rise in the Parisian society of the 19th century. The digital edition of these more than 3 000 fully-transcribed letters, initially published on the correspondancefamiliale.ehess.fr website, was threatened in the short term due to the end of life of its support software, Lodel. The outcome of this work is a renewed publication using Semantic MediaWiki, which publishes this corpus in a version enriched with a large number of semantic relations linking the letters and their actors within a knowledge graph exposed on the Web of data. These links are exploited to build a dynamic database of authors and recipients along with people mentioned in the letters and the places from which they were sent. The digitised texts and facsimiles are made available under an open licence on the research repositories Zenodo (doi: 10.5281/zenodo.5810596) and Didomena (doi: 10.25721/wr4c-3e07).